Use of a New Gas Ejector for a TEG/TREG Natural Gas Dehydration System - Marcin Bernat; Stanisław Nagy; Rafał Smulski (Energies, 2023)
Glycol dehydration is the most common and economical water removal method from natural gas streams. However, dehydration of low-pressure natural gas requires the use of higher concentration TEG (Triethylene Glycol) or TREG (Tetraethylene Glycol). This article describes how the ejector can be used to create a vacuum in the glycol reboiler to achieve a higher concentration of L-TEG/L-TREG (Lean Triethylene Glycol/Lean Tetraethylene Glycol). Process simulations of the gas dehydration and glycol regeneration units were carried out in Chemcad software. Simulations were performed for decreasing values of gas working pressure and TEG/TREG regeneration pressures. Dehydration unit efficiency was tested for two values of glycol flow rates. Ejector performance simulations were executed for two positions in the process flow line. The influence of pressure reduction in the glycol reboiler on the concentration of L-TEG/L-TREG and the water dewpoint of natural gas has to be found significant. The increase in glycol flow rate has a greater impact on TREG than for TEG. Creating a vacuum with an ejector in a TEG/TREG reboiler has been shown to be an attractive way to improve the efficiency of natural gas dehydration. The position of the ejector at the end of the vapor flow line, downstream to the condensed water separator, allows for a significant reduction in motive gas consumption.